Salinity and freshwater discharge determine rotifer distribution at the Mossoró River Estuary (Semiarid Region of Brazil) - Medeiros,AMA. (2010)
The present study aimed at evaluating differences in rotifer distribution in three estuarine zones in an inverse estuary located in the Semiarid Region of Brazil. Zones were chosen based on their proximity to the ocean and river border as a means of reflecting a horizontal salinity gradient. High freshwater discharge during the rainy season was the major determinant of rotifer composition. On the other hand, due to higher salinity values during the dry season, very low values of species richness and abundance were observed in all zones. Therefore, the study highlights the constraints of salinity and the positive influence of seasonality and river proximity on rotifer species in a semiarid estuarine environment.